Immunotherapy for gastric cancers: emerging role and future perspectives. Issue 6 (3rd June 2017) - Bonotto, Marta; Garattini, Silvio Ken; Basile, Debora; Ongaro, Elena; Fanotto, Valentina; Cattaneo, Monica; Cortiula, Francesco; Iacono, Donatella; Cardellino, Giovanni Gerardo; Pella, Nicoletta; Fasola, Gianpiero; Antonuzzo, Lorenzo; et al.
ABSTRACT: Introduction : The broad use of immunotherapy is revolutionizing the treatment paradigms of many solid tumors. Although chemotherapy remains the treatment backbone for advanced gastric cancer, improvements in its molecular characterization and progresses in understanding its underpinning biology have supported clinical development of novel immunotherapies. However, the results of recent trials testing these new agents raise the question on how to identify the patients that could greatly benefit. Areas covered : This article summarizes the current understanding on the biology and the mechanisms underlying different clinical features of gastric cancers. Particularly, after a comprehensive literature search, we speculate whether specific molecular subsets of patients could derive more benefit from immunotherapy. Expert commentary : Most cancers may evade the immune response, which is normally regulated by a delicate balance between activating and inhibitory signals. For example, both CTLA-4 and PD-1, once linked to PD-L1/2, may inhibit T-cell signaling. The use of agent to harness the power of the immune system appears to be the ultimate frontier in gastric cancer treatment. While anti-CTLA-4 antibodies are minimally active, there is growing evidence for the efficacy of PD1/-L1 inhibitors. The search of predictive factors for immunotherapy will provide key hints towards the optimal use of these agents.